The Influence of Cultural Values and Value of Children on Mother's Time Allocation at Cimanuk Watershed Families - Dwi Ajeng Larasati; Hartoyo Hartoyo (Journal of Family Sciences, 2016)
The purpose of this research were to describe the cultural values, the value of children and mother's time allocation for children at Cimanuk watershed and to analyze the effect of family characteristic, cultural values, and value of children toward time allocation of mothers to children at Sundanese and Javanese. This research involved 200 families who have children below five years old selected with purposive method. The samples were interviewed by using structure questionnaire. The result of this research showed that there was no significant different on the perception of the value of children between Sundanese and Javanese families. Regression analysis showed that mother's time allocation for children was influenced by the age of children, the length of mother's education, the mother's occupation, the uncertainty avoidance and power distance dimension of cultural values.